2021
DOI: 10.1186/s13584-021-00473-x
|View full text |Cite|
|
Sign up to set email alerts
|

Physical activity, resilience, emotions, moods, and weight control, during the COVID-19 global crisis

Abstract: Objectives This study aimed at exploring the relationships between physical activity, weight control, and psycho-social aspects of the COVID-19 lockdown, which have characterized the Israeli population’s behavior during the COVID-19 global crisis. Design Cross-sectional survey research. Methods Participants included 1855 men and women aged 18 and above, from different regions in the country and represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…The pandemic had an effect of health behaviors of the general population: A survey among Israeli adults demonstrated that more people stopped engaging in routine PA compared with those who began exercising during the lockdown. A higher percentage of people reported weight gain than those who reported weight loss [ 53 ]. The pandemic also had an effect on the health of children and adolescents, pointing to even greater importance of student guidance to lead a healthy lifestyle: In a large (N=37K) retrospective cohort study in Israel, the pandemic correlated with overall weight gain among children and adolescents [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic had an effect of health behaviors of the general population: A survey among Israeli adults demonstrated that more people stopped engaging in routine PA compared with those who began exercising during the lockdown. A higher percentage of people reported weight gain than those who reported weight loss [ 53 ]. The pandemic also had an effect on the health of children and adolescents, pointing to even greater importance of student guidance to lead a healthy lifestyle: In a large (N=37K) retrospective cohort study in Israel, the pandemic correlated with overall weight gain among children and adolescents [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zach et al. ( 2021 ) found that people who were physically active during the lockdown period reported a higher level of resilience and positive feelings, and a lower level of depression, compared with those who were not physically active. Furthermore, they found that changes in PA habits from being active prelockdown to becoming inactive during lockdown were related to increased depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…were closed, people were allowed to be physically active. Current studies indicate that being physically active is positively associated with mental health, well-being, and quality of life under the pandemic/lockdown conditions and can help to cope with the challenges arising from the pandemic situation and its restrictions in everyday life (Brailovskaia et al., 2021 ; Maher, Hevel, Reifsteck, & Drollette, 2021 ; Mata et al., 2021 ; Zach, Fernandez-Rio, Zeev, Ophir, & Eilat-Adar, 2021 ). In contrast, social activities, such as meeting family and friends, going to bars, etc., were not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified that an incorrect version of Fig. 1 was published.…”
Section: Correction To: Israel Journal Of Health Policy Research (2021) 10:52 Https://doiorg/101186/s13584-021-00473-xmentioning
confidence: 99%
“…1186/ s13584-021-00473-x. *Correspondence: simaz@wincol.ac.il 1 The Academic College at Wingate, Wingate Institute, 4290200 Netanya, Israel Full list of author information is available at the end of the article Author details 1 The Academic College at Wingate, Wingate Institute, 4290200 Netanya, Israel. 2 Universidad de Oviedo, Oviedo, Spain.…”
Section: Open Accessmentioning
confidence: 99%